A conceptual model for take-home workplace exposures. Issue 1 (2nd January 2018) - Jones, Rachael M.; Burstyn, Igor
ABSTRACT: The boundary between occupational and environmental exposures is often artificial, as occupational hazards can readily escape the workplace. One way that this occurs is when workers "take-home" occupational hazards, exposing family members. While take-home exposures have long been recognized, there is no comprehensive framework describing the pathways by which workers bring home workplace hazards. In this article, we provide such a conceptual model that includes three pathways for take-home exposures: external contamination, internal dose, and behavior change of workers. This conceptual model should help to describe the problems of take-home exposures more comprehensively in future research.